2016
DOI: 10.1016/j.plaphy.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a is a favorable substrate for Chlamydomonas Mg-dechelatase encoded by STAY-GREEN

Abstract: Mg removal from chlorophyll by Mg-dechelatase is the first step of chlorophyll degradation. Recent studies showed that in Arabidopsis, Stay Green (SGR) encodes Mg-dechelatase. Though the Escherichia coli expression system is advantageous for investigating the properties of Mg-dechelatase, Arabidopsis Mg-dechelatase is not successfully expressed in E. coli. Chlamydomonas reinhardtii SGR (CrSGR) has a long, hydrophilic tail, suggesting that active CrSGR can be expressed in E. coli. After the incubation of chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…A previous study showed that CrSGR has the same catalytic properties as Arabidopsis SGR (AtSGR)1 and that transiently expressed CrSGR ‐induced Chl degradation in Arabidopsis (Matsuda et al ., ). In this study, CrSGR was constitutively expressed in an Arabidopsis sgr triple mutant using the 35S promoter (CrSGR‐35S) or an Arabidopsis native promoter (2 kbp upstream from the translation start site of AtSGR1 ) (CrSGR‐N) (Figure S7).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…A previous study showed that CrSGR has the same catalytic properties as Arabidopsis SGR (AtSGR)1 and that transiently expressed CrSGR ‐induced Chl degradation in Arabidopsis (Matsuda et al ., ). In this study, CrSGR was constitutively expressed in an Arabidopsis sgr triple mutant using the 35S promoter (CrSGR‐35S) or an Arabidopsis native promoter (2 kbp upstream from the translation start site of AtSGR1 ) (CrSGR‐N) (Figure S7).…”
Section: Resultsmentioning
confidence: 97%
“…By contrast, Chl b is not present in the core antenna complexes of streptophytes, including Arabidopsis, and SGR can degrade all the Chl in the core antennae, which might be one of the reasons why SGR has different physiological functions between Arabidopsis and Chlamydomonas . It should be noted that AtSGR1 and CrSGR catalyze the same reaction that converts Chl a to Pheo a but not chlorophyllide a to pheophorbide a (Matsuda et al ., ). In addition, CrSGR partly complemented an Arabidopsis sgr triple mutant (Figure S7), and transiently expressed CrSGR in Arabidopsis induced Chl degradation (Matsuda et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations